Direct Bilirubin Levels Predict Long-Term Outcomes in Patients With Acute Coronary Syndrome Under Different Glucose Metabolism Status: A 6.5-Year Cohort Study of Three-Vessel Disease - Liu, Yue; Zhang, Ce; Jiang, Lin; Tian, Jian; Zhao, Xue-yan; Xu, Jing-jing; Liu, Ru; Xu, Bo; Hui, Ru-tai; Gao, Run-lin; Yuan, Jin-qing; Xu, Lian-jun; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: There is controversy over the relationship between bilirubin and coronary artery disease. This study aimed to evaluate the predictive value of direct bilirubin (DB) in patients with complex acute coronary syndrome (ACS). Methods: From April 2004 to February 2011, 5322 ACS patients presenting with 3-vessel disease were consecutively enrolled. Disease severity and complexity were determined by SYNTAX score (SS) and SS II. The primary endpoint was all-cause death and the secondary endpoints were major adverse cardiovascular and cerebrovascular events (MACCE). Stratification of normal glucose regulation, pre-diabetes, and diabetes was based on a previous diagnosis, hypoglycemic medications, fasting blood glucose, and hemoglobin A1c. Results: Subjects were divided into quartiles according to baseline DB (μmol/L): Q1 (0-1.6), Q2 (1.61-2.20), Q3 (2.21-2.80), and Q4 (>2.80). Multivariable logistic regression analysis showed that DB was an independent predictor of intermediate-high SS. During a median follow-up time of 6.5 years, elevated DB was associated with more all-cause death (p<0.001) but not MACCE. DB remained to be predictive of all-cause death in multivariable Cox regression model (Q2vs Q1: HR 1.043, 95%CI 0.829-1.312, p=0.719; Q3 vs Q1: HR 1.248, 95%CI 1.001-1.155, p=0.048, Q4 vs Q1: HR 1.312, 95%CI 1.063-1.620, p=0.011). When stratifying subjects according to glucose metabolism regulation and treatment strategies, the predictivity of DB was only profound in patients with diabetes or with conservative treatment. Additionally, incorporating DB further improved the discrimination and reclassification abilities of SS II for risk prediction. Conclusion: DB is a potential biomarker for predicting lesion severity and long-term outcomes in ACS patients.